Nilai-Nilai Psikologi Religius dalam al-Qur’an dan Relevansinya terhadap Pembentukan Karakter Santri - Dedi Mustofa (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This study explores the values of Qur’anic religious psychology and their relevance to character formation among students (santri) at Pondok Pesantren Hidayatul Mubarok, Central Lampung, Indonesia. Amidst the moral crises affecting today’s youth, the Qur’an is viewed as a comprehensive source of spiritual-psychological guidance. Employing a qualitative-descriptive approach, the study integrates field research and library analysis, using a thematic (mawḍū‘ī) tafsir method to identify psychological values embedded in Qur’anic verses. The findings reveal that Qur’anic concepts such as ṣabr (patience), ikhlāṣ (sincerity), tawakkul (trust in God), shukr (gratitude), and khauf–rajā’ (fear–hope balance) significantly contribute to shaping students’ ethical and emotional maturity. In the pesantren setting, these values are internalized through structured religious learning, moral habituation, and the exemplary conduct of teachers. Activities such as sorogan and bandongan foster both cognitive and affective development, while the pesantren’s environment reinforces discipline and spirituality. The study concludes that religious psychological values derived from the Qur’an play a fundamental role in cultivating akhlāq al-karīmah (noble character) among santri and offer an integrative model of character education rooted in Islamic tradition.